Delays in cancer diagnosis: challenges and opportunities in Europe - Renzi, Cristina; Odelli, Stefano; Morani, Federica; Benitez Majano, Sara; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Early cancer diagnosis is a public health priority, but large proportions of patients are diagnosed with advanced disease or as an emergency, even in countries with universal healthcare coverage. The study aimed at examining factors contributing to diagnostic delays and inequalities in cancer care, discussing challenges and opportunities for improving the diagnosis of cancer. Methods: We performed a critical review of the literature examining factors contributing to delays and inequalities in cancer diagnosis, published between 2019-2023, in Europe with a specific focus on Italy. Results: Disparities in screening, cancer diagnosis and treatment have been reported in many European countries, with poorer outcomes for some population sub-groups. For example, some Northern regions in Italy have six-times higher screening participation versus Southern regions. In 2019 36% of the Italian population aged 50-74 reported colorectal cancer screening, higher than the EU average (33%), but lower than in countries like Denmark (>60%). In Italy, the EU country with the largest percentage of people aged 65+, incident cancers are expected to rise by 19.6% over two decades. Older age is also associated with multimorbidity, with physical and mental health morbidities possibly affecting cancer diagnostic pathways. For example, colon cancer patients with pre-existing mental health conditions were 28% less likely to have a prompt colonoscopy when presenting with red-flag symptoms, according to recent UK research. Covid-19 has exacerbated pre-existing inequalities, with reductions in scheduled surgery and oncological treatments, especially affecting women, older and less educated individuals. Conclusions: For ensuring appropriate care, it is crucial to better understand how different factors, including physical and mental health morbidities, impact cancer diagnosis. The “NextGenerationEU” program and the “National Recovery and Resilience Plan” (PNNR in Italy) following the Covid-19 pandemic offer opportunities for reducing inequalities, improving cancer care and chronic disease management for ageing populations.